Effects of patin fish oil and turmeric extract on levels of malondialdehyde and superoxide dismutase in wistar rat models of metabolic syndrome - Ni Nengah Asti Kartika Sari; Mohammad Sulchan; Diana Nur Afifah (AcTion: Aceh Nutrition Journal, 2024)
Increased oxidative stress in metabolic syndrome conditions leads to increased malondialdehyde and decreased superoxide dismutase. Patin fish oil (Pangasius hypophthalmus) and turmeric extract (Curcuma longa Linn.) contain bioactive compounds that play a role in improving malondialdehyde and superoxide dismutase levels. The research obtained to measure the effectiveness of patin fish oil, turmeric extract, and their combination against MDA and SOD levels. The research applied an experimental design of randomized pre-post test control groups. Research location at PSPG Animal Laboratory, UGM Yogyakarta in August to October 2023. Wistar male white rats (thirty rats) were randomly divided into five groups, namely K- (Normals), K+ (HFFD), P1(HFFD+catfish oil dose of 0,08 ml/200grBB), P2(HFFD+turmeric extract dose of 5,04 mg/kgBB), and P3(HFFD+catfish oil dose of 0,08 ml/200grBB+turmeric extract dose of 5,04 mg/kgBB). Intervention for 28 days. Information analysis utilizing combined t-test and one-way ANOVA test taken after by post-hoc test. Outcome, catfish oil, turmeric extract, and their combination of them all had an significant effects on MDA levels (p=0,000) and SODs (p=0,000). The mean reduce in MDA levels and increment in SOD were more prominent in P3, which amounted to 5,29±0,28 nmol/ml and 22,62±7,03 units/ml. In conclusion, catfish oil and turmeric extract successfully decrease MDA and increment SOD. The combination of both have the potential to improve metabolic syndrome.